Analisis Neraca Perdagangan Indonesia-India Periode 2013-2018 - Mohammad Yusuf; Dewi Mahrani Rangkuty (Jurnal Penelitian Medan Agama, 2019)
This study aims to find out the Analysis of Trade, Exports, Imports on the Indonesia-India Trade Balance, Period 2013-2018. As independent variables in this study are Trade, Export and Import. While the dependent variable is the Trade Balance.The research uses the data analysis method used is associative / quantitative research which is analyzed by descriptive statistics in this test using the E-Views program. In addition to using descriptive statistical test tools also use the Classical Assumption test. The classic assumption test used includes normality test, multicollinearity test, linearity test and autocorrelation test. Meanwhile, the test of goodness of fit test uses an interpretation formula, namely interpretation of the R value (coefficient of determination), interpretation of the F test (Fisher) and interpretation of the t test.Meanwhile the data used in this study are secondary data sourced from the Department of Commerce and BPS which are analyzed using quantitative methods with a descriptive approach and the study population is a report on Analysis of Trade, Exports, Imports on the Indonesia-India Trade Balance, 2013-2018.The results of this study conclude that the trade sector has a positive and significant effect on the trade balance, the export sector has a positive and insignificant effect on the trade balance, the import sector has a negative and significant effect on the trade balance.